Energy management and power quality improvement of microgrid system through modified water wave optimization - Subhashree Choudhury; George Tom Varghese; Satyajit Mohanty; Venkata Ratnam Kolluru; Mohit Bajaj; Vojtech Blazek; Lukas Prokop; Stanislav Misak (Energy Reports, 2023)
A comparative study of energy management strategies and PQ improvement schemes for a Fuel Cell, Battery, and SuperCapacitor integrated Microgrid system has been projected utilizing the MATLAB/Simulink architecture in this research article. For effective energy management and PQ enhancement, a Modified Water Wave Optimization algorithm based on adaptive population size and adaptive wavelength coefficient has been proposed. The MWWO method robustly and dynamically tunes the parameters of the Proportional Integral controller for effective operation. The efficiency of the proposed technique has been compared with the traditional methods regarding hydrogen consumption, load power deliberation, power quality and overall system efficiency. The results obtained and the numerical analysis confers the superiority of the suggested technique over other methods for enhanced dynamic voltage response, low fuel consumption, reduced harmonics and better efficacy thereby proving its real-time employment.